Pengaruh Penggunaan Game Online terhadap Perilaku Remaja di Desa Lamunga Kecamatan Taliwang Kabupaten Sumbawa Barat - Parhun, Muhammad; Mawaddah, Ida Aulia (FONDATIA, 2025)
The widespread use of online games among adolescents has sparked various social debates, highlighting the need for empirical studies on its impact. This study aims to analyze the influence of online game usage on adolescent behavior in Lamunga Village, Taliwang District, West Sumbawa Regency. A quantitative approach was employed using simple linear regression analysis. The results indicate that online game usage does not have a significant influence on adolescent behavior. This is reflected in the coefficient of determination (R Square) value of 0.151, suggesting that only 15.1% of the variation in adolescent behavior can be explained by online game usage, while the remaining 84.9% is influenced by other factors not covered in this study. These findings imply that although online gaming is a prominent phenomenon, its impact on adolescent behavior is not isolated and must be understood within the broader context of social, environmental, and psychological factors.